Repeats identification using improved suffix trees. (11th December 2009) - Huo, Hongwei; Wang, Xiaowu; Stojkovic, Vojislav
The suffix tree data structure plays an important role in the efficient implementations of some querying algorithms. This paper presents the fast Rep(eats)Seeker algorithm for repeats identification based on the improvements of suffix tree construction. The leaf nodes and the branch nodes are numbered in different ways during the construction of a suffix tree and extra information is added to the branch nodes. The experimental results show that improvements reduce the running time of the RepSeeker algorithm without losing the accuracy. The experimental results coincide with the theoretical expectations.